2020
DOI: 10.1039/d0cc03920a
|View full text |Cite
|
Sign up to set email alerts
|

A bis(germylene) functionalized metal-coordinated polyphosphide and its isomerization

Abstract: Pentaphosphaferrocene, [Cp*Fe(η5-P5)], was used as an air-stable source of polyphosphorus units to synthesize a novel bis(germylene)-functionalized transition metal polyphosphide complex, which further undergoes a unique constitutional isomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
3
15
0
6
Order By: Relevance
“…A similar structural motif of the latter complexes was already reported for the cationic rhodium complex [(triphos)Rh(η 2 :η 1 ‐P 4 RR′)] + with overall P−P distances closely related to those observed for 8 a [24] . Note that, for [Cp*Fe(η 4 ‐P 5 {GeL} 2 )] (L=( t BuN) 2 CPh), a migration of one exocyclic germylene fragment towards the Cp*Fe unit was observed [25] . The mixed phosphorus and arsenic complexes 9 a – c and 10 a – c expand the series of rare examples of complexes comprising mixed polypnictogen ligands, namely, EP 3 (E=As, Sb), [2] [Cp′′′Co(μ 3 ,η 4 :η 1 :η 1 ‐AsP 4 Cp*){W(CO) 5 } 2 ], [9] [(Cp′′′Fe) 2 (μ,η 4 :η 4 ‐P x As y )] ( x + y= 4), [Cp′′′Fe(η 5 ‐P x As y )] ( x + y= 5) [26] and [{Cp R Mo(CO) 2 } 2 (μ,η 2 :η 2 ‐EE′)] (E/E′=P, As, Sb, Bi) [27] were reported.…”
Section: Resultssupporting
confidence: 78%
“…A similar structural motif of the latter complexes was already reported for the cationic rhodium complex [(triphos)Rh(η 2 :η 1 ‐P 4 RR′)] + with overall P−P distances closely related to those observed for 8 a [24] . Note that, for [Cp*Fe(η 4 ‐P 5 {GeL} 2 )] (L=( t BuN) 2 CPh), a migration of one exocyclic germylene fragment towards the Cp*Fe unit was observed [25] . The mixed phosphorus and arsenic complexes 9 a – c and 10 a – c expand the series of rare examples of complexes comprising mixed polypnictogen ligands, namely, EP 3 (E=As, Sb), [2] [Cp′′′Co(μ 3 ,η 4 :η 1 :η 1 ‐AsP 4 Cp*){W(CO) 5 } 2 ], [9] [(Cp′′′Fe) 2 (μ,η 4 :η 4 ‐P x As y )] ( x + y= 4), [Cp′′′Fe(η 5 ‐P x As y )] ( x + y= 5) [26] and [{Cp R Mo(CO) 2 } 2 (μ,η 2 :η 2 ‐EE′)] (E/E′=P, As, Sb, Bi) [27] were reported.…”
Section: Resultssupporting
confidence: 78%
“…Ein ähnliches Strukturmotiv wie für letztere Komplexe wurde bereits für den kationischen Rhodiumkomplex [(triphos)Rh(η 2 :η 1 ‐P 4 RR′)] + mit P‐P‐Abständen, die sehr nahe bei den für 8 a beobachteten liegen, berichtet [24] . Man beachte, dass für [Cp*Fe(η 4 ‐P 5 {GeL} 2 )] (L=( t BuN) 2 CPh) eine Migration eines exocyclischen Germylen‐Fragments in Richtung der Cp*Fe‐Einheit beobachtet wurde [25] . Die gemischten Phosphor‐ und Arsenkomplexe 9 a – c und 10 a – c erweitern die Reihe der seltenen Beispiele von Komplexen, die gemischte Polypnictogenliganden enthalten, wo EP 3 (E=As, Sb), [2] [Cp′′′Co(μ 3 ,η 4 :η 1 :η 1 ‐AsP 4 Cp*){W(CO) 5 } 2 ], [9] [(Cp′′′Fe) 2 (μ,η 4 :η 4 ‐P x As y )] ( x + y= 4), [Cp′′′Fe(η 5 ‐P x As y )] ( x + y= 5) [26] und [{Cp R Mo(CO) 2 } 2 (μ,η 2 :η 2 ‐EE′)] (E/E′=P, As, Sb, Bi) [27] berichtet wurden.…”
Section: Ergebnisse Und Diskussionunclassified
“…In 2020, Roesky et al reported the reactivity of [Cp*Fe(η 5 -P 5 )] with these germylenes and the isolation of a bis(germylene)incorporated transition metal polyphosphide complex A (Chart 1), where P is between two Ge atoms. 7 In 2020, Li et al presented the reaction of trichlorogermanium-substituted monogermylene with Me 3 SiN 3 azide affords compound PhC(N t Bu) 2 Ge−N(TMS)-GeL 3 (B), where an organic azide is inserted between two Ge atoms. 8 In 2014, Power and coworkers presented the insertion of two nitrogen between two Ge atoms leads to a four-membered Ge 2 N 2 ring compound (C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The lower reactivity of [PhC­(N t Bu) 2 Ge–Ge­(N t Bu) 2 CPh] compared to that of [PhC­(N t Bu) 2 Si–Si­(N t Bu) 2 CPh] could be helpful to observe some intermediates that were predicted to be formed but could not be detected. In 2020, Roesky et al reported the reactivity of [Cp*Fe­(η 5 -P 5 )] with these germylenes and the isolation of a bis­(germylene)-incorporated transition metal polyphosphide complex A (Chart ), where P is between two Ge atoms . In 2020, Li et al presented the reaction of trichlorogermanium-substituted monogermylene with Me 3 SiN 3 azide affords compound PhC­(N t Bu) 2 Ge–N­(TMS)-GeL 3 ( B ), where an organic azide is inserted between two Ge atoms .…”
Section: Introductionmentioning
confidence: 99%